2010
DOI: 10.1139/h10-039
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prekallikrein levels are positively associated with circulating lipid levels and the metabolic syndrome in children

Abstract: Plasma prekallikrein (PK) has been shown to be associated with cardiovascular disease (CVD) and its risk factors, but these associations have not been investigated in children. The present study examined PK activity in relation to well-established cardiovascular risk factors in a cohort of children aged 9–11 years (N = 97). We found a significant and positive association between PK and fasting levels of total cholesterol (p < 0.01), non-high-density lipoprotein cholesterol (p < 0.01), and triglycerides (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The serum level of PK is positively correlated with low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG) but not with high-density lipoprotein cholesterol (HDL-C) in young adult Han Chinese (aged 17–25 years). A previous study also demonstrated similar correlations in children aged 9–11 years [ 9 ]. This means that an increase in serum PK levels leads to increased lipid levels, thus leading to an increased occurrence of hyperlipidemia.…”
Section: Introductionsupporting
confidence: 75%
“…The serum level of PK is positively correlated with low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG) but not with high-density lipoprotein cholesterol (HDL-C) in young adult Han Chinese (aged 17–25 years). A previous study also demonstrated similar correlations in children aged 9–11 years [ 9 ]. This means that an increase in serum PK levels leads to increased lipid levels, thus leading to an increased occurrence of hyperlipidemia.…”
Section: Introductionsupporting
confidence: 75%
“…Plasma PK level was also found to be positively correlated with circulating LDL-C in children. 39 Moreover, several KLKB1 variants have been reported to be associated with coronary artery disease. Suhre et al 40 reported that rs4253252 of KLKB1 had a weak association with coronary artery disease in the CARDIOGRAM study (Coronary Artery Disease Genome-Wide Replication and Meta-Analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma kallikrein levels were associated with the risk of CVD and stroke in men, and individuals who experienced an MI had higher levels of plasma kallikrein (21,22). Children with abnormal lipid profiles and metabolic syndrome had elevated plasma kallikrein levels that were associated with CVD risk factors (23). Furthermore, polymorphisms in plasma kallikrein (rs3733402) that results in reduced plasma kallikrein activity are associated with reduced CVD risk (24).…”
Section: Discussionmentioning
confidence: 99%